Iman Dalam Penderitaan: Kajian Biblika Kitab Ayub 1-2 Sebagai Upaya Peneguhan Iman Kristiani - Jean Tris Zalukhu; Iwan Setiawan Tarigan; Ratna Saragih (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The purpose of this research is to know Job’s faith in the suffering of the Book of Job 1-2 and the efforts to strengthen the Christian faith based on Job’s faith in suffering. The research method of this paper is a qualitative method with a literature study approach. The research was conducted by observing various literature texts according to the topic of discussion in the research. The results of the study show that there are various steps that can be implemented in an effort to strengthen Christian faith based on the book of Job 1-2, namely: living in fear of God, recognizing God’s sovereignty in life and having the right perspective on God’s actions and decisions in life.